A review on the effect of planting density and planting material towards yield production in oil palm plantation / Muhammad Nur Hidayat Ismail - Ismail, Muhammad Nur Hidayat (Faculty of Plantation and Agrotechnology, 2018)
Oil palm, currently the world’s main vegetable oil crop, is characterized as a large productivity and a long-life span commodity. Peak oil yields of 12 t ha−1 yr−1 have been achieved in small plantations and maximum theoretical yields as calculated with simulation models are 18.5 t oil ha−1 yr−1, yet average productivity worldwide has stagnated around 3 t oil ha−1 yr−1. In this review, an overview of the available data on yield determining presented about factors which focused on planting density and planting material method. Different planting densities and planting materials had been studied to show the effect towards yield in oil palm plantation. From the review, the information resulted by the comparison between previous researches will be able to provide the best planting density and planting material to the oil palm plantation company. There are some differences on yield when applying different densities in cultivating the oil palm. The mean of Fresh Fruit Bunch (FFB), Number of Bunch (BNO), Average Bunch Weight (ABW), and the mean of Oil Yield (OY) be the indicator to show the effect of the planting density towards yield. In order to determine effect of planting material towards, the oil to bunch percentage, oil yield and fresh fruit bunch was analyzed. From this study, the best planting density is depending on the condition of the soil. At rate 148 palms/ha it is suitable for inland, while 170 palms/ha for riverine alluvium, and 200 palms/ha for peat soil. The best planting material is clone P164 which is produced by MPOB because it can generate high oil yield, very low mantling rate and ease in tissue culturing.